The impact of education for sustainable development on university students’ sustainability behavior: a case study from undergraduate students in Somalia - Abdullahi, Abdulkadir Mohamed; Hussein, Hassan Abdikadir; Ahmed, Mohamed Yusuf; Hussein, Omar Ahmedqani; Warsame, Abdimalik Ali (Frontiers in Education, 2024)
Education plays a crucial role in moving towards a sustainable future. The United Nations Decade of Education for Sustainable Development has advocated education for sustainable development to promote global sustainability. UNESCO supports ESD as a way to provide society with the knowledge, skills, values, and attitudes needed for sustainable living. While considerable progress has been made in many developed countries, particularly in higher education institutions, and to some extent in developing countries, similar success has not been observed in Somalia's higher education establishments. This study examined the influence of Education for Sustainable Development on university students' conduct in Somalia. Through cluster sampling, 251 students from SIMAD and Hormuud Universities in Mogadishu were chosen to participate by completing a questionnaire. The research revealed a significant positive connection between Education for Sustainable Development and students' behavior. The findings emphasize the importance of integrating Education for Sustainable Development into higher education curricula to encourage cultural norms that endorse environmentally friendly practices. This investigation offers valuable insights for academics, policymakers, and businesses seeking to advance sustainability within educational settings and beyond.